Accidental Explantation of a Cochlear Implant in a Child Who Developed Cholesteatoma as a Late Complication of Cochlear Implantation. (9th October 2020) - Low, Wong Kein; Pok, Wan Ni; Ng, Win Nie; Tan, Judy
Abstract : Introduction . Although rare, cholesteatoma can develop as a late complication of cochlear implantation. The electrode array may then be exposed in the external auditory canal surrounded by cholesteatoma debris. Case Report . The cochlear implant of a child was inadvertently explanted by a clinician during a routine aural toilet procedure. The child had previously reported recurrent ear infections, pain, and unexplained implant function degradation. Reimplantation was carried out 2 days later with good postoperative hearing results. Part of the electrode array was observed to be embedded in cholesteatoma. Postreimplantation recovery was complicated by a breakdown of the blind-sac. Discussion . Clinical indicators that could alert the clinician to the possibility of this late complication include recurrent infections, presence of keratotic debris in the external auditory canal, unexplained implant function degradation, and nonauditory stimulation. Although this patient managed to achieve excellent postreimplantation hearing outcomes, a delay in reimplantation surgery following explantation could possibly compromise successful reinsertion of the electrode array. External ear canal overclosure without mastoid cavity obliteration has merit in facilitating CT scan surveillance, but it may increase the risk of the blind-sac breaking down. This case also illustrated how the electrode array could have facilitated propagation of the cholesteatoma from the middle ear to the mastoid. Conclusion . If aural toilet is required in the implanted ear of a cochlear implant recipient, any complaint of hearing change, pain, or discharge should alert the clinician of the possibility of cholesteatoma developing. It warrants prompt evaluation by an experienced otologist in order to prevent accidental explantation. Keywords . Cochlear implant, cochlear implant complications, chronic suppurative otitis media, cholesteatoma, reimplantation, blind-sac, external auditory canal overclosure, mastoid cavity obliteration.